2022
DOI: 10.1128/spectrum.01402-21
|View full text |Cite
|
Sign up to set email alerts
|

The Comparability of Anti-Spike SARS-CoV-2 Antibody Tests is Time-Dependent: a Prospective Observational Study

Abstract: This work showed that the comparability of apparently standardized SARS-CoV-2 antibody assays (Roche, Abbott; both given in BAU/mL) after vaccination depends on the time of blood withdrawal. Initially (3 weeks after the first dose AZD1222), there were 3 times higher values in the Abbott assay, but this relationship inversed before boosting (11 weeks after the first dose) with Roche 2 times greater than Abbott.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 56 publications
4
15
0
1
Order By: Relevance
“…Differentiating high- and low-affinity antibodies may have significant clinical implications, since lower serum IgG avidity is likely associated with higher risk of infection [33] . Our study also showed that the correlation of antibodies between two assays became stronger with time following the vaccination, which is consistent with the results from a previous study [27] . Factors other than the affinity/avidity maturation of antibodies that may affect the kinetics of antibody following vaccination require further evaluation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Differentiating high- and low-affinity antibodies may have significant clinical implications, since lower serum IgG avidity is likely associated with higher risk of infection [33] . Our study also showed that the correlation of antibodies between two assays became stronger with time following the vaccination, which is consistent with the results from a previous study [27] . Factors other than the affinity/avidity maturation of antibodies that may affect the kinetics of antibody following vaccination require further evaluation.…”
Section: Discussionsupporting
confidence: 93%
“…However, at 6 months, few participants met the criterion for seroprotection according to the Architect assay, while 43% of participants met the criterion according to the Elecsys assay. A previous study measuring anti-RBD antibody titers after vaccination with a viral-vector vaccine also showed differences in kinetics between titers measured by the Architect assay and those measured by the Elecsys assay [27] . These results suggest that it is not appropriate to determine the timing of booster vaccination based on the results of only one type of immunoassay.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, our method highly correlated with the Abbott assay ( R 2 = 0.936). Since the antibody detection by Abbott and Roche assays has different dynamic ranges, the correlation depends on the sampling time of blood [ 3 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…All other currently authorized tests are qualitative or semi-quantitative [2]. Antibody-testing technologies are mainly categorized into (a) single-use lateral flow tests (immunochromatography), where the presence of antibodies is demonstrated by a color change on a paper strip, and (b) laboratory-based immunoassays that allow the processing of many specimens simultaneously [3,4]. In addition, some microarray systems have been developed for research purposes [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The following steps might be necessary to achieve consensus on the correlates of protection [281][282][283]:…”
Section: Challenges To the Collection And Interpretation Of Seroepide...mentioning
confidence: 99%